The Exchange of Social Support on Online Bariatric Surgery Discussion Forums: A Mixed-Methods Content Analysis. Issue 5 (4th May 2018) - Atwood, Molly E.; Friedman, Aliza; Meisner, Brad A.; Cassin, Stephanie E.
ABSTRACT: Bariatric surgery patients often experience physical and psychosocial stressors, and difficulty adjusting to significant lifestyle changes. As a result, social support groups that provide patients with support, coping skills, and nutritional information are valuable components of bariatric care. Support group attendance at bariatric centers is associated with greater post-surgery weight loss; however, several barriers hinder attendance at in-person support groups (e.g., travel distance to bariatric centers). Consequently, online support forums are an increasingly utilized resource for patients both before and after surgery. This study examined and described the type and frequency of social support provided on a large online bariatric surgery forum. A total of 1, 412 messages in the pre- ( n = 822) and post-surgery ( n = 590) sections of the forum were coded using qualitative content analysis according to Cutrona and Suhr's (1992) Social Support Behavior Code model (i.e., including informational, tangible, esteem, network, and emotional support types). The majority of messages provided informational and emotional support regarding: a) factual information about the bariatric procedure and nutrition; b) advice for coping with the surgery preparation process, and physical symptoms; and c) encouragement regarding adherence to surgical guidelines, and weight loss progress. Network, esteem, and tangible support types were less frequent than informational and emotional support types. The results inform healthcare providers about the types of social support available to bariatric patients on online support forums and, thus, encourage appropriate referrals to this resource.